Real-world outcomes in non-endemic hereditary transthyretin amyloidosis with polyneuropathy: a 20-year German single-referral centre experience - Ungerer, Matthias; Hund, Ernst; Purrucker, Jan; Huber, Laura; Kimmich, Christoph; Siepen, Fabian aus dem; Hein, Selina; Kristen, Arnt; Hinderhofer, Katrin; Hayes, Jennifer; Schönland, Stefan; Hegenbart, Ute; et al. (Amyloid, 2021)
Hereditary transthyretin amyloidosis is caused by pathogenic variants in the TTR gene and typically manifests, alongside cardiac and other organ dysfunctions, with a rapidly progressive sensorimotor and autonomic polyneuropathy (ATTRv-PN) leading to severe disability. While most prospective studies have focussed on endemic ATTRv-PN, real-world data on non-endemic, mostly late-onset ATTRv-PN are limited. This retrospective study investigated ATTRv-PN patients treated at the Amyloidosis Centre of Heidelberg University Hospital between November 1999 and July 2020. Clinical symptoms, survival, prognostic factors and efficacy of treatment with tafamidis were analysed. Neurologic outcome was assessed using the Coutinho ATTRv-PN stages, and the Peripheral Neuropathy Disability (PND) score. Of 346 subjects with genetic TTR variants, 168 patients had symptomatic ATTRv-PN with 32 different TTR variants identified. Of these, 81.6% had the late-onset type of ATTRv-PN. Within a mean follow-up period of 4.1 ± 2.8 years, 40.5% of patients died. Baseline plasma N-terminal prohormone of brain natriuretic peptide (NT-proBNP) ≥900 ng/l (HR 3.259 [1.421-7.476]; p = .005) was the main predictor of mortality in multivariable analysis. 64 patients were treated with tafamidis and presented for regular follow-up examinations. The therapeutic benefit of tafamidis was more pronounced when treatment was started early in ATTRv-PN stage 1 (PND scores II vs. I; HR 2.718 [1.258-5.873]; p = .011). In non-endemic, mostly late-onset ATTRv-PN, cardiac involvement assessed by NT-proBNP is a strong prognosticator for overall survival. Long-term treatment with tafamidis is safe and efficacious. Neurologic disease severity at the start of treatment is the main predictor for ATTRv-PN progression on tafamidis.
Gesehen am 24.04.2024